Accessory head of flexor digiti minimi: a case study - Vanguri Sailabala; Manasa Bethi (Wolters Kluwer Medknow Publications, 2015)
Flexor digiti minimi is a muscle of hypothenar eminence. It flexes the little finger at metacarpophalangeal joint. During routine Anatomical dissection, an extra muscle was noticed in the flexor compartment of right forearm of a male cadaver. The identified muscle took origin from medial aspect of the Palmaris longus tendon just proximal to the wrist joint. When traced distally this muscle joined the fibers of the Flexor digiti minimi,and finally got inserted to palmar aspect of base of proximal phalanx of 5th digit.In its course, the muscle crossed median nerve and Ulnar artery. Because of this reason, this variation has the potential to cause compression of the structures mentioned above and is of interest to clinicians.